Investigating the relationship between miRNA expression and epithelial mesenchymal transition in colorectal cancer - Jaca, Anelisa (Division of Anatomical Pathology, 2017)
Introduction: Epithelial-mesenchymal transition (EMT) is characterized by the loss of an epithelial phenotype and gain of a mesenchymal phenotype, i.e., migratory and metastatic properties. The EMT process is therefore characterized by a low expression of E-cadherin and high expression of mesenchymal markers (e.g., N-cadherin, snail and vimentin). It is stated that cells which have undergone EMT also gain stem cell features. Therefore, both EMT and stem cell phenotypes have been implicated in carcinogenesis and metastasis of tumour cells. Furthermore, EMT is regulated by small non-coding molecules (miRNAs) that either function as tumour suppressors or oncogenes (oncomirs). Tumour suppressor miRNAs reverse EMT while oncomirs activate it. Therefore, investigating the relationship between miRNAs and EMT is important in addressing metastasis of colorectal cancers (CRC). Aims and Objectives: The aim of the study was to determine the association between miRNA (miRNA-21 and miRNA-34a) expression levels and EMT in CRC. In addition, this investigation aimed to correlate miRNA and EMT data with clinicopathologic features of the study cohort. Methodology: A total of 100 CRC (including 8 known HNPCC cases) Formalin Fixed Paraffin Embedded (FFPE) tissue blocks and their corresponding H&E slides were collected from the archives of the Division of Anatomical Pathology at the University of Cape Town. Subsequently, the FFPE tissue blocks were sectioned at 3μm and IHC analysis of 4 EMT markers (E-cadherin, N-cadherin, snail-1 and vimentin) and 1 stem cell marker (CD44V6) was performed. The stains were then evaluated and scored by a pathologist. The IHC data were then correlated with clinicopathologic features. Furthermore, 59 cases (FFPE tissues and corresponding H&E slides) which included the 8 HNPCCs were randomly selected for miRNA analysis. The H&Es were examined by a pathologist to demarcate normal and tumour regions. RNA was then extracted from 59 tumours and 12 normal tissues using a High Pure FFPET Isolation Kit (Roche). Subsequently, cDNA was synthesized and qRT-PCR was performed to determine the expression levels of miRNA-21 and miRNA-34a. MiRNA-21 and miRNA-34a expression levels were ascertained using the relative quantification method. Moreover, the clinical significance of the two miRNAs was evaluated in relation to MSI status. Therefore, IHC analysis of MLH1, MSH2 and MSH6 mismatch repair proteins was performed on the Ventana platform. Statistical analysis was performed using Fisher's and Pearson's Chi Square tests in Stata 12 to correlate EMT and clinicopathologic data. Additionally, the Mann-Whitney non-parametric test in GraphPad prism 6 was used to determine miRNA-21 and miRNA-34a expression in relation to EMT and MSI data. Results: Our results showed low expression of E-cadherin in 77% of cases. In addition, there was decreased expression of N-cadherin and vimentin in 98% whilst snail-1 expression was decreased in 65% of the cases. Low expression of CD44v6 was also seen in 78% of the cases. There was no correlation between EMT/stem cell markers and clinicopathologic data. Furthermore, increased miRNA-21 expression was significantly associated with grade, lymph node metastasis and age of patients. There was a significant correlation between high miRNA- 21 expression and down-regulated snail-1 and N-cadherin expression. MiRNA-34a expression was not associated with any of the clinicopathologic features. In addition, high miRNA-34a expression was linked with low expression of snail-1 and CD44v6. Increased miRNA-21 expression was related with MSS tumours, whereas there was no relationship between miRNA- 34a and MSI status. Conclusion: Our investigation shows that there is an inverse association between miRNA (miRNA-21 and miRNA-34a) expression and two EMT (N-cadherin and snail-1) markers in our colorectal cancer cohort. Our data also show that both miRNA-21 and miRNA-34a cannot be used as biomarkers to determine progression of the cancer. Contrary to previous studies, our findings indicate that miRNA-21 does not activate EMT in this CRC cohort. However, similar to other studies our results confirm that miRNA-34a may be repressing snail-1 expression, thereby inhibiting EMT in the cancer.